THE PREVALENCE OF HETEROTOPIC OSSIFICATION AMONG PATIENTS AFTER CERVICAL DISK ARTHROPLASTY AT 5 YEARS - Stepanov,Ivan Andreevich (2021)
ABSTRACT Objective: This study was designed to evaluate the prevalence and grading of heterotopic ossification (HO) at five years, among patients after cervical disk arthroplasty (CDA). Methods: The CDA procedure with Activ C and M6-C prostheses was performed on 127 patients. The mean age of the cohort of patients was 38.4 years (range 18-49). The mean follow-up time was 58.4 months, ranging from 51 to 66 months. Results: Grade 1 ossifications were present in 11 (8.6 %) levels. A total of 45 (35.4 %) segments showed grade 2 HO. HO that led to restrictions in range of motion were present in 13 (10.2 %) cases. Five years after surgery, 9 (7.0 %) patients with grade 4 ossifications were found only in the M6-C artificial disk prosthesis group. In the analysis of patient survival following the occurrence of HO, all patients showed median survival of 28.3±5.6 months. The group that received the Activ C artificial disk prosthesis showed statistically longer survival (49.5±7.8 months) than the M6-C disk group. Conclusions: In our study 61.4% of patients exhibited HO after a mean follow-up of 58.4 months. In the analysis of patient survival after HO, all patients showed median survival of 28.3±5.6 months. The group that received the Activ C artificial disk prosthesis showed statistically longer survival (49.5±7.8 months) than the M6-C disk group. Level of evidence III; Cross-sectional Observational Study.